2016
DOI: 10.1097/md.0000000000002461
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Intercondylar Humeral Fractures With 3D-Printed Osteosynthesis Plates

Abstract: The aim of the study was to evaluate the efficacy custom 3D-printed osteosynthesis plates in the treatment of intercondylar humeral fractures.Thirteen patients with distal intercondylar humeral fractures were randomized to undergo surgery using either conventional plates (n = 7) or 3D-printed plates (n = 6) at our institution from March to October 2014. Both groups were compared in terms of operative time and elbow function at 6 month follow-up.All patients were followed-up for a mean of 10.6 months (range: 6–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 17 publications
2
59
0
2
Order By: Relevance
“…The authors considered this approach efficacious and ready for evaluation in a larger population. 3D printed plates for fixation of intercondylar humeral fractures have also been used (126). Within orthopedic surgery, 3D printing has also been used to fabricate custom external fixation hardware.…”
Section: Anatomic Models: Pre-surgical Manipulation and Selection Of mentioning
confidence: 99%
“…The authors considered this approach efficacious and ready for evaluation in a larger population. 3D printed plates for fixation of intercondylar humeral fractures have also been used (126). Within orthopedic surgery, 3D printing has also been used to fabricate custom external fixation hardware.…”
Section: Anatomic Models: Pre-surgical Manipulation and Selection Of mentioning
confidence: 99%
“…The use of 3D printing for planning of complex surgery is one aspect, Jeong et al 4 reported using this technique to perform accurate pre‐bending of osteosynthesis plates to allow minimally invasive fracture repair. The other main application is the creation of custom devices, which can reduce operative time and improve outcomes 5,6 . Additive manufacture using metals is the most relevant for implant fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study integrated 3D printing and computer aided design to produce a 3D printed personalized titanium plate for the surgical resection of bone tumors and the results indicated that the use of such a plate could significantly improve the clinical outcomes in the surgical removal of bone tumor 21 . Another study conducted by Shuang et al 22 found that 3D printed plates are safe and effective for the treatment of intercondylar humeral fractures and using them can significantly reduce operative time.…”
Section: Therapeutic Effect Evaluationmentioning
confidence: 99%